Further insight into the mechanism of poly(styrene‐co‐methyl methacrylate) microsphere formation. Issue 13 (20th April 2017) - Applin, Samantha I.; Schmitz, Russell C.; Tiemsin, Pacita I.; Genzer, Jan; Connell, John W.; Wohl, Christopher J.
ABSTRACT: Polymeric microspheres have been used in a broad range of applications from chromatographic separation techniques to analysis of air flow over aerodynamic surfaces. The preparation of microspheres from many polymer families has consequently been extensively studied using a variety of synthetic approaches. Although there are a myriad of polymeric microsphere synthesis methods, free‐radical initiated emulsion polymerization is one of the most common techniques. In this work, poly(styrene‐ co ‐methyl methacrylate) microspheres were synthesized via surfactant‐free emulsion polymerization. The effects of co‐monomer composition and addition time on particle size distribution, particle formation, and particle morphology were investigated. Particles were characterized using dynamic light scattering and scanning electron microscopy to gain further insight into particle size and size distributions. Reaction kinetics were analyzed through consideration of characterization results. A particle formation mechanism for poly(styrene‐ co ‐methyl methacrylate) microspheres was proposed based on characterization results and known reaction kinetics. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2249–2259 Abstract : Poly(styrene‐ co ‐methyl methacrylate) microspheres were synthesized via surfactant‐free emulsion polymerization. The effects of co‐monomer composition and the addition time on particle size distribution, particle formation, and particle morphology were investigated using dynamic light scattering and scanning electron microscopy. Reaction kinetics was analyzed alongside characterization, and a particle formation mechanism was proposed.